NGO and its impact on political democratization and economic development Focusing on Leyte Rural Advancement Program (LRAP). - Ty, John Benedict C. (Tacloban City John Benedict C. Ty, 2009)
This study centers on Leyte Rural Advancement Program (LRAP), a nongovernmental organization focusing on rural development. NGOs have different and various undertakings, but all aim at improving the quality of life. Some NGOs in particular focus on rural development and consequently become vital in community development. NGOs focusing on rural development therefore play an important role in the development of the quality of life of members of rural communities. Despite the vast array of researches regarding rural development and NGOs, there is little known about local NGOs and other organizations which provide support for rural development. LRAP has been studied under four major indicators namely: (1) Distributive Justice or Equity; (2) Institutional and Sectoral Capacity; (3) People's Participation or Participatory Approach; and (4) Self-Reliance and Ecological Balance, or Sustainability. LRAP has also been situated in the national and regional setting of rural development NGOs. Since the nature of the study is strictly qualitative, it heavily relied on interviews of key individuals like officers and members of LRAP, the members of the rural communities, and other individuals. In conclusion, LRAP has generally been able to provide positive change and development to its target group, the underprivileged farmer sector, although these positive developments are hindered by a number of factors. These impediments include: LRAP's lack of resources and limited funding; weakening participation among the members of the communities; and some other significant problems. But considering all the circumstances, LRAP is a relatively successful organization for the reason that it has achieved its main goal of developing agro-industrial rural communities, providing these communities with the capacity to transform indigenous resources into goods and services without adverse effects on the environment, and to provide sustainability, self-sufficiency, self-reliance, and self-governance among the members of these communities.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science